Employee job satisfaction case study at Bank Kerjasama Rakyat Berhad Wilayah Selatan Area / Mohamad Abu Bakar Baharuddin - Baharuddin, Mohamad Abu Bakar (Faculty of Business and Management, 2011)
This paper aims to identify the factors that determine employee job satisfaction towards Bank Kerjasama Rakyat Berhad Wilayah Selatan area. It was held among the residents that reside within Wilayah Selatan territory. The population of this research is among 555 employees that work in twenty three (23) territories under Wilayah Selatan area, and researchers choose only 100 respondents by using simple random sampling. The variable that has been tested in this study is employee of Bank Kerjasama Rakyat in Wilayah Selatan area. The type of analysis in this research involving Pearson correlation and multiple regression analysis. It is found that, there is a significant relationship between, working environment, salary and career development towards job satisfaction in Bank Kerjasama Rakyat Berhad Wilayah Selatan area excepted job rotation that does not have significant relationship between job rotation.